A Comparison of Indonesian and US Labor Law Regarding the Economic Exploitation of Child Labor in the Entertainment Industry - Tasya Shavina Putri; Elisabeth Septin Puspoayu (NOVUM : JURNAL HUKUM, 2024)
Children working in the entertainment industry have a high potential for economic exploitation by parents and employers. The problem formulations in this research are: (1) How is the comparison of labor law in Indonesia and the United States related to the economic exploitation of child labor in the entertainment industry, (2) How is the comparison of formulations related to the economic exploitation of child labor in entertainment between Indonesian and United States labor law? The purpose of this study is to analyze the comparison of labor law in Indonesia and the United States related to the economic exploitation of child labor in the entertainment industry. The research method used is legal research using a statutory approach and a comparative approach. The results of the study can be concluded that in Indonesia itself the regulations related to economic exploitation of child labor are still vague, there are no concrete limits related to economic exploitation, while one of the states of California has the Coogan Law which protects child artists from economic exploitation. Changes to laws and regulations in Indonesia are carried out by inserting or adding material to laws and regulations and deleting or replacing some of the material of laws and regulations, while in the United States it is done by members of the House of Representatives or Senate distributing the Draft Law or asking other members through Dear Colleague Letters to sign the draft.